1986
DOI: 10.1002/j.1460-2075.1986.tb04431.x
|View full text |Cite
|
Sign up to set email alerts
|

The reaction site of a non-competitive antagonist in the delta-subunit of the nicotinic acetylcholine receptor.

Abstract: A site in the primary structure of the nicotinic acetylcholine receptor from Torpedo marmorata covalently labeled with the non-competitive antagonist [3H]triphenylmethylphosphonium (TPMP+) was localized. The label was found in position 262 of the 6-polypeptide chain. This site is specifically labeled in the presence of the agonist carbamoylcholine. Labeling is prevented by the non-competitive antagonist histrionicotoxin. Position 262, probably a serine, is located in the highly conserved membrane-spanning heli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(33 citation statements)
references
References 13 publications
3
30
0
Order By: Relevance
“…The results of covalent labeling with CPZ and triphenylmethylphosphonium provide convergent evidence that segments M2 are potential components of the ion translocation device. Consistent with this view, site-directed mutagenesis experiments have shown, following the original observation of Giraudat et al [I] and Oberthiir et al [13], that a region of the ~-subunit comprising segment M2 and the portion between segments M2 and M3 contribute to the regulation of ion transport [32]. More recent works from the same groups have shown that clusters of charged residues neighbouring both ends of segment M2 of the a-, fl-, 7"-and d-subunits are major determinants of the rate of ion transport [33].…”
Section: Analysis Of Cnbr Sub Fragments Of the Tryptic Digestsupporting
confidence: 66%
See 2 more Smart Citations
“…The results of covalent labeling with CPZ and triphenylmethylphosphonium provide convergent evidence that segments M2 are potential components of the ion translocation device. Consistent with this view, site-directed mutagenesis experiments have shown, following the original observation of Giraudat et al [I] and Oberthiir et al [13], that a region of the ~-subunit comprising segment M2 and the portion between segments M2 and M3 contribute to the regulation of ion transport [32]. More recent works from the same groups have shown that clusters of charged residues neighbouring both ends of segment M2 of the a-, fl-, 7"-and d-subunits are major determinants of the rate of ion transport [33].…”
Section: Analysis Of Cnbr Sub Fragments Of the Tryptic Digestsupporting
confidence: 66%
“…Furthermore, electrophysiological (review in [27][28][29]) as well as biochemical (review in [6,30]) evidence supports the view that the high-affinity NCB site is located within the ion channel. Photoactivatable NCBs are thus useful tools for direct identification of potential channel-forming elements within each of the AChR subunits [1,2,12,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure was essentially as described before [6]. The photolabeled receptor-rich membranes were dissolved in sample buffer and the polypeptide chains were separated in two steps by preparative SDS-polyacrylamide gel electrophoresis, using the apparatus from BRL, Bethesda.…”
Section: Purification Of Rh]tpmp+ -Labeled Subunitsmentioning
confidence: 99%
“…Noncompetitive antagonists, a very heterogenous group of compounds, are thought to be tools for its elucidation because they block ion fluxes by sterically or allosterically interacting with the channel [4]. Recently a binding site for the noncompetitive antagonists chlorpromazine [5] and TPMP+ [6] has been localized in the S-subunit of AChR from Torpedo marmorata by photoaffinity labeling and microsequencing work. It was identified as serine 262 located in the membranespanning helix II (according to the five-helix model proposed by Finer-Moore and Stroud [7] and Guy [S]).…”
Section: Introductionmentioning
confidence: 99%